ESTABLISHMENT OF AUTHORITARIAN REGIME THROUGH POLITICAL TRANSFORMATION (ON THE EXAMPLE OF CENTRAL ASIA) - Боринська, О. Л. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Reformation of any political system occurs in several stages and one of the constituents of transformation is the establishment of the concept of political elections. This investigation helps uncover tendencies in artificial consolidation and personification of the presidential power by formal application of election procedures and referendums.